World drug report 2008 - Oficina de las Naciones Unidas contra la Droga y el Delito (UNODC) (2008)
Indicators of the world drug situation remain favourable over the long-term, but there are recent warning signs that must be heeded. A global and long-term perspective reveals that illicit drug use has been contained to less than 5% of the adult population (yearly incidence rate for people aged 15-64). In other words, less than one in every twenty people used illicit drugs at least once in the past 12 months. Problem drug users (people severely drug dependent) are limited to less than one tenth of this already low percentage: there may be 26 million of them, about 0.6% of the planet’s adult population.